The Fate Of Water In The Oasis Of Ouakda Between Traditional Systems And Modern (region Of Béchar, Southwest, Algeria) - Rezzoug, C.; Remini, B.; Hamoudi, S. (University of Eloued جامعة الوادي, 2017)
One of the subjects that touch the field of environment is undoubtedly the traditional catchment systems and drainage divide in the oasis. The ancestral techniques such as wells chadouf, quanat, Khettara and foggaras have protected the oasis and the man in the past. These techniques were used in an arid middle by the oasis dwellers and resisted to a hostile climate for centuries. In spite of the low rainfall in the region of our oasis, the oasis dwellers of Ouakda through their intelligence, they were able to cultivate their land without disturbing a fragile ecosystem through exploitation of groundwater table thanks to the use of foggaras with the small distance which does not exceed 100 m. But the intervention of modern systems of water catchment like deep boreholes which overexploiting nonrenewable tablecloths and the pumps large capacity, the man has completely destroyed a clean environment. Today, thanks to these pumping, the groundwater level has dropped considerably; soil salinity is remarkable on all the parcels of the old palm grove and the Oued. We try in this Article to study the history of traditional techniques of water catchments in the oasis of Ouakda, to do a comparison between the ancestral systems used in the another oasis in this oasis, to study the impact of the motor pumps on the degradation of traditional systems and detrimental effects (Soil salinity and the phenomenon of lowering of the groundwater) after the use of modern techniques of water catchment.
Article in Journal of Fundamental and Applied Sciences Vol 09, N 01
Keywords: Oasis, Ouakda, Foggara, Wells, Chadouf, motor pump.